1998
DOI: 10.1143/jjap.37.4482
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Oxygen-Containing Pt and Pt Oxide Thin Films by Reactive Sputtering and Their Characterization

Abstract: Oxygen-containing Pt and Pt oxide thin films were prepared by reactive sputtering in Ar and O2 gas atmosphere and effects of oxygen flow ratio on crystallinity, chemical bonding state and resistivity were studied. Polycrystalline oxygen-containing Pt and amorphous Pt oxide thin films were obtained at O2 flow ratios below 20% and above 30%, respectively. It is confirmed that these films are composed of the mixture of Pt, PtO and PtO2 and the oxygen content in these films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 12 publications
3
19
0
Order By: Relevance
“…Then the silicon substrates covered with an annealed SiO 2 buffer layer were placed standing against the walls of the closed Pyrex bottle. 18 The observed oxygen content is higher than the stoichiometric concentration, which may be attributed to absorption and surface contamination of the sample. The as-synthesized products were subsequently dried in air and analyzed by field-emissionscanning electron microscope ͑FE-SEM; JEOL, JSM-6700F͒ operated at 3.0-5.0 keV, X-ray diffractometer ͑XRD; MAC Science, MXP 18X͒ using Cu K␣ radiation ͑ = 1.540 52 Å͒, transmission electron microscope ͑TEM; JEOL, JEM-2010͒ operated at 200 keV, energy dispersive X-ray spectroscopy ͑EDS͒ attached to the JEM-2010, and X-ray photoelectron spectroscopy ͑XPS; Physical Electronics, PHI 1600͒ using Mg K␣ radiation.…”
Section: Methodsmentioning
confidence: 90%
“…Then the silicon substrates covered with an annealed SiO 2 buffer layer were placed standing against the walls of the closed Pyrex bottle. 18 The observed oxygen content is higher than the stoichiometric concentration, which may be attributed to absorption and surface contamination of the sample. The as-synthesized products were subsequently dried in air and analyzed by field-emissionscanning electron microscope ͑FE-SEM; JEOL, JSM-6700F͒ operated at 3.0-5.0 keV, X-ray diffractometer ͑XRD; MAC Science, MXP 18X͒ using Cu K␣ radiation ͑ = 1.540 52 Å͒, transmission electron microscope ͑TEM; JEOL, JEM-2010͒ operated at 200 keV, energy dispersive X-ray spectroscopy ͑EDS͒ attached to the JEM-2010, and X-ray photoelectron spectroscopy ͑XPS; Physical Electronics, PHI 1600͒ using Mg K␣ radiation.…”
Section: Methodsmentioning
confidence: 90%
“…Figure 4 shows the temperature dependence of oxygen impurities analyzed by a depth profile of secondary ionmass spectrography ͑SIMS͒. The oxygen impurities are thought to adsorb on the grain boundaries similar to a sputter-deposited platinum film in an oxygen-containing atmosphere, 9 because the platinum metal is not oxidized to PtO at temperatures below 400°C in the ambient pressure. [9][10][11][12] The oxygen impurities decrease with an increase in the deposition temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The oxygen impurities are thought to adsorb on the grain boundaries similar to a sputter-deposited platinum film in an oxygen-containing atmosphere, 9 because the platinum metal is not oxidized to PtO at temperatures below 400°C in the ambient pressure. [9][10][11][12] The oxygen impurities decrease with an increase in the deposition temperature. It was reported that the surface morphology of Pt CVD films was smoother due to the reduction of their surface and grain boundary energies as the amount of oxygen gas was increased during the deposition.…”
Section: Resultsmentioning
confidence: 99%
“…This matches well with the resistivity values reported in the literature. 44,45 For the Pt_20R and Pt_30R samples, we estimate the resistivity of PtO/PtO 2 to be 7 Â 10 À4 X m. This increase in conductivity is attributed to the built-in electric field generated by Pt-PtO/PtO 2 junction as illustrated in Fig. 8(c).…”
Section: Electrical Characterizationmentioning
confidence: 95%
“…Abe et al 44,45 have also evaluated Platinum oxide films and demonstrated that the PtO is metallic but PtO 2 is semiconducting in nature with a bandgap of 1.2 eV-1.5 eV. PtO 2 can be prepared using a variety of techniques such as chemical process, 41-43 reactive sputtering of Pt, [44][45][46] or oxygen plasma treatment of Pt [47][48][49] thin films. In this work, we create PtO 2 nanostructures with an embedded Pt core, in-situ, during the reactive ion etching (RIE) of Si/SiO 2 to achieve suspended core-shell structure.…”
Section: Introductionmentioning
confidence: 99%